SUCCESSFUL CORRECTION OF PARTIAL ANOMALOUS DRAINAGE OF PULMONARY VEINS INTO THE SUPERIOR VENA CAVA (World Bulletin of Public Health, 2023)
This scientific paper describes the authors' experience in the correction of partial anomalous pulmonary vein drainage (PAPVD) in an adult patient. The types of surgery and long-term results in PAPVD in adults are analyzed on the basis of the literature review. The relative rarity of clinical observations of PAPVD in patients over 30 years old is due to the isolated form of malformation without pulmonary vein obstruction and concomitant CHD. The experience with PAPVD correction in adult patients is limited to single surgeries; according to the literature, most adult patients with PAPVD come to the attention of cardiologists and cardiac surgeons after 20 years of age. Therefore, study of clinical course and diagnostic methods of PAPVD in adult patients is relevant to enable timely detection of the defect, rational planning of examination and selection of optimal correction method
Keywords: congenital heart disease in adults; surgery of partial anomalous pulmonary vein drainage; radiography; findings